Algorithm Implementation of the Onboard Control Complex Arbitration Subsystem - Hrushko, Svitlana; Zeleneva, Irina; Kirichek, Galina; Timenko, Artur (2020 IEEE 15th International Conference on Advanced Trends in Radioelectronics, Telecommunications and Computer Engineering (TCSET), 2020)
The subject of research in this article is the arbitration subsystem algorithm of the configuration control module (CCM), as a part of the complex CCM algorithm. The number and size of the used chips is very important for the devices used on satellites. At the same time, redundancy methods are widely used to ensure the reliability of these devices, which lead to an increase in the hardware amount. The article considers the possibility of using a combined finite state machine (CFSM) to implement the arbitration subsystem algorithm of the onboard control complex and to use the field programmable gate array (FPGA) structural features to reduce the hardware amount both for CFSM and CCM implementation.